2022
DOI: 10.3390/ijerph19159658
|View full text |Cite
|
Sign up to set email alerts
|

Market Women’s Perspectives on Coronavirus Disease 2019 (COVID-19): The Case of Ghana and South Africa

Abstract: Globally, countries are still battling health challenges and the negative economic stress on the citizenry caused by COVID-19. This study explored the perspectives of market women in Ghana and South Africa on COVID-19. Data collection was executed in both Ghana and South Africa between March 2021 and December 2021. Employing semi-structured questionnaires, face-to-face interviews were conducted. Most of the market women in Ghana described COVID-19 as a global pandemic, while market women in South Africa descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another assessment of the adequacy of pre-pandemic social protection programs and the CAP concluded that the government's response to COVID-19 and the lockdown "was devoid of any organizational framework and thus became a classic case of crisis management" [41]. The lockdown, coupled with the fact that the CAP provided no support for micro-enterprises in the informal sector or those working in formal employment who were laid off, led to business failure and hardship for women market traders [42].…”
Section: Covid-19 In Ghanamentioning
confidence: 99%
“…Another assessment of the adequacy of pre-pandemic social protection programs and the CAP concluded that the government's response to COVID-19 and the lockdown "was devoid of any organizational framework and thus became a classic case of crisis management" [41]. The lockdown, coupled with the fact that the CAP provided no support for micro-enterprises in the informal sector or those working in formal employment who were laid off, led to business failure and hardship for women market traders [42].…”
Section: Covid-19 In Ghanamentioning
confidence: 99%
“…5.3.3 | Gender discrimination and vulnerability in health care, sexual, and reproductive health Access to quality health care is critical during the pandemic, and women and girls are less likely to have it, especially in rural and marginalized communities including the markets. During the pandemic, women in market places were vulnerable to the spread of the virus due to a lack of adequate preventive measures such as face masks, hand sanitizers, and general PPEs (Frimpong et al, 2022). Again, they did not practice social distancing as was well done in the formal sector.…”
Section: Gender Discrimination and Vulnerability In Income Work And E...mentioning
confidence: 99%